Launching Hagar : Marginality, Beer-Sheva, Critique - Yiftachel, Oren (Hagar: Studies in Society and Culture, 2000)
The article discusses various reports published with the issue, including the topic by Jean and John Comaroff on the analysis of boarder panic on post-colonial state, the study to construct a multi-layered citizenship by Nira Yuval-Davis and the criticisms of Peter Marcuse on the overlaps between identity and territory.